2022
DOI: 10.3390/brainsci12070906
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of Frameless Robot-Assisted Deep Brain Stimulation and Accuracy Compared with the Frame-Based Technique

Abstract: Background: Frameless robot-assisted deep brain stimulation (DBS) is an innovative technique for leads implantation. This study aimed to evaluate the accuracy and precision of this technique using the Sinovation SR1 robot. Methods: 35 patients with Parkinson’s disease who accepted conventional frame-based DBS surgery (n = 18) and frameless robot-assisted DBS surgery (n = 17) by the same group of neurosurgeons were analyzed. The coordinate of the tip of the intended trajectory was recorded as xi, yi, and zi. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Upon evaluating the titles and abstracts, a total of 116 publications were determined to be irrelevant and thus excluded. After a comprehensive inspection of the entire text, a total of 16 articles (Delavallee et al, 2016;Lefranc et al, 2017;Ho et al, 2018Ho et al, , 2019VanSickle et al, 2019;Faraji et al, 2020;Jin et al, 2020;Paff et al, 2020;Eross and Halasz, 2021;Ribault et al, 2021;Liang et al, 2022;Mei et al, 2022;Soler-Rico et al, 2022;Hegde et al, 2023;Wu et al, 2023) were chosen for inclusion in this meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon evaluating the titles and abstracts, a total of 116 publications were determined to be irrelevant and thus excluded. After a comprehensive inspection of the entire text, a total of 16 articles (Delavallee et al, 2016;Lefranc et al, 2017;Ho et al, 2018Ho et al, , 2019VanSickle et al, 2019;Faraji et al, 2020;Jin et al, 2020;Paff et al, 2020;Eross and Halasz, 2021;Ribault et al, 2021;Liang et al, 2022;Mei et al, 2022;Soler-Rico et al, 2022;Hegde et al, 2023;Wu et al, 2023) were chosen for inclusion in this meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…Frontiers in Aging Neuroscience 08 frontiersin.org Mei et al, 2022;Chuang et al, 2023;Hegde et al, 2023;Li, 2023;Schulder et al, 2023) when DBS was performed by conventional frame-based stereotactic methods. The vector error was quantified at 1.09 mm in individuals with PD who underwent robot-assisted DBS, according to our findings.…”
Section: Figurementioning
confidence: 99%
“…They found that the accuracy and precision of wire implantation in the frameless robot-assisted DBS surgery with awake state is equivalent to that in the traditional frame-based technology, and the vector error and coordinate error of the target point implanted with the electrode assisted by the frameless robot have no statistical significance with the traditional frame implantation (p = 0.13). 39 Compared with foreign robots, SR1 has reached the world’s advanced level in error value with its 1.52 ± 0.53mm vector error. Previously, it was reported that some foreign research centers regarded 3 mm as the standard for implanting wires, while most studies believed that the accuracy below 2 mm was the ideal choice for wire placement.…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Nine studies reported data on this method, with a target radial error of 0.91 ± 0.38 mm (n = 819 electrodes), operative time of 109.1 ± 50.5 minutes (n = 659), and total procedure time of 249.2 ± 72.3 minutes (n = 265). 5,[17][18][19][20][21][22][23] Four studies reported their use of a skull-mounted robot with optical array registration/navigation, with a target radial error of 1.12 ± 0.54 mm (n = 406 electrodes), operative time of 155.4 ± 36.5 minutes (n = 406), and total procedure time of 277.1 ± 38.2 minutes (n = 165). 7,[24][25][26] Three studies (including this study) reported the use of a floor-mounted robot with a frameless transient fiducial array, with a target radial error of 0.84 ± 0.54 mm (n = 631 electrodes), operative time of 182.4 ± 47.8 minutes (n = 315), and total procedure time of 311.9 ± 63.0 min (n = 315).…”
Section: Meta-analysismentioning
confidence: 99%